Effect of naproxen on the hypothalamic–pituitary– adrenal axis in healthy volunteers - Eijsbouts, Agnes M M (Blackwell Science Inc, 2009)
AIM: To study the effect of the nonsteroidal anti-inflammatory drug naproxen on the activity of the hypothalamic–pituitary–adrenal (HPA) axis in healthy volunteers. METHODS: A double-blind, randomized study in two groups of 20 healthy volunteers was performed. The activity of the HPA axis was measured before and after the use of naproxen or placebo during a period of 2 weeks. Basal plasma adrenocorticotropic hormone (ACTH) and cortisol, 24-h urinary cortisol, and circadian cortisol rhythm in saliva were determined. Plasma ACTH and cortisol were also measured during submaximal physical exercise. RESULTS: There were no significant differences between the placebo and naproxen groups in basal plasma ACTH [09.00 h 3.1 pmol l(−1), 95% confidence interval (CI) 2.0, 4.2, and 2.8 pmol l(−1), 95% CI 1.9, 3.7, respectively], cortisol levels (09.00 h 0.45 µmol l(−1), 95% CI 0.39, 0.51, and 0.40 µmol l(−1), 95% CI 0.35, 0.44, respectively), 24 h urinary cortisol excretion (67.5 nmol 24 h(−1), 95% CI 54.3, 80.7, and 86.8 nmol 24 h(−1), 95% CI 54.4, 119.2, respectively), circadian cortisol rhythm measured in salivary samples, or ACTH and cortisol concentrations after physical exercise. After the use of placebo or naproxen for 2 weeks, no significant change in any of the parameters occurred (ACTH 09.00 h 3.0 pmol l(−1), 95% CI 2.0, 3.9, and 3.0 pmol l(−1), 95% CI 2.2, 3.8, respectively; cortisol 09.00 h 0.45 µmol l(−1), 95% CI 0.37, 0.52, and 0.39 µmol l(−1), 95% CI 0.34, 0.44, respectively; cortisol urine 79.5 nmol 24 h(−1), 95% CI 59.5, 99.4, and 81.7 nmol 24 h(−1), 95% CI 64.0, 99.4, respectively), and no significant differences were found in these parameters between the placebo and naproxen groups. CONCLUSIONS: The use of naproxen does not influence the activity of the HPA axis in healthy volunteers under basal circumstances or in response to physical stress.